Impact of body mass index on development of nontuberculous mycobacterial pulmonary disease. Issue 2 (4th February 2021) - Song, Jin Hwa; Kim, Bong Seong; Kwak, Nakwon; Han, Kyungdo; Yim, Jae-Joon
The incidence and prevalence of nontuberculous mycobacterial pulmonary disease (NTM-PD) have been increasing worldwide. The risk of NTM-PD may be higher in undernourished populations. In this study, we tried to elucidate the impact of body mass index (BMI) and its change on development of NTM-PD. We performed a retrospective cohort study including South Koreans aged >40 years who underwent biennial National Health Insurance System (NHIS) health check-ups in both 2005 and 2009 or 2006 and 2010. We monitored eligible individuals from the study initiation date (NHIS health check-up date in 2009 or 2010) until the diagnosis of NTM-PD or until December 31, 2017. Enroled individuals were classified based on BMI at initiation date. By calculating hazard ratios, we compared NTM-PD incidence per 100 000 person-years by BMI group and by BMI change. A total of 5 670 229 individuals were included in the final analysis. Compared with the BMI <18.5 kg·m −2 group, the incidence of NTM-PD gradually decreased with increased BMI (adjusted hazard ratio 0.38, 95% confidence interval (CI) 0.35–0.42 for BMI 18.5–22.9; 0.17, 95% CI 0.15–0.19 for BMI 23–24.9; 0.1, 95% CI 0.09–0.11 for BMI 25–29.9; and 0.1, 95% CI 0.07–0.13 for BMI ≥30). A BMI decrease of ≥1 kg·m −2 over 4 years increased the incidence of NTM-PD (adjusted hazard ratio 1.08, 95% CI 1.01–1.16) whereas a BMI increase of ≥1 kg·m −2 decreased the incidence of NTM-PD (adjusted hazard ratio 0.77, 95% CI 0.71–0.83). In conclusion, BMI was inversely related to development of NTM-PD and weight loss increased the risk of NTM-PD. Higher body mass index was protective against development of nontuberculous mycobacterial pulmonary disease (NTM-PD) among Korean people. Weight loss increased the risk of NTM-PD. https://bit.ly/2PDawxn